Association Between Year of Birth and 1-Year Survival Among Extremely Preterm Infants in Sweden During 2004-2007 and 2014-2016. Issue 1 (March 2020) - Norman, M.; Hallberg, B.; Abrahamsson, T.; Björklund, L.J.; Domellöf, M.; Farooqi, A.; Foyn Bruun, C.; Gadsbøll, C.; Hellström-Westas, L.; Ingemansson, F.; Källén, K.; Ley, D.; et al.
Abstract : ( JAMA . 2019;321(12):1188–1199) Since 2004-2007, Sweden has created new recommendations, regulations and laws concerning extremely preterm births. In 2008, it became mandatory to register all stillbirths at 22 to 27 weeks' gestational age to record statistics for all extremely preterm births. The withholding or withdrawal of advanced life support was the subject of regulations issued in 2011. In 2016, national guidelines for perinatal management were published and included recommendations on the resuscitation of infants delivered between 22 and 24 weeks gestation, the use of antenatal corticosteroid treatment, mode of delivery, and centralization of care. It's unclear if these actions had significant effects on outcomes for extremely preterm infants in Sweden. This study aimed to compare the survival rates of extremely preterm infants born in 2004-2007 with those born between 2014 and 2016.